Polemik Penghidupan Kembali Pengamanan Swakarsa: Dilema antara Community Policing dan Vigilantisme [Controversy Surrounding the Reestablishment of Civil Security Forces (Pam Swakarsa): a Dilemma Between Community Policing and Vigilantism] - Rafi Damar Bungsadewo; Nabila Indah Chairunnisa; Shofiyah Adila Farhana (Sekretariat Jenderal DPR RI, 2021)
Currently, the issue of civil security forces Pam Swakarsa has been raised in public discourse and becomes the Indonesian National Police’s primary program as an effort to implement community policing, a paradigm that emphasizes partnership between national police and the community as an element of voluntary security. However, the bad reputation of Pam Swakarsa in 1998 as a group of lawless vigilantes behind some of the human rights violations has posed a challenge for the police to revive Pam Swakarsa. The Indonesian Pasukan Pengamanan Swakarsa, better known as Pam Swakarsa, played an important role in securing the Special Session of the People’s Consultative Assembly (MPR RI) in 1998. Historically, prior to the formation of Pam Swakarsa, voluntary security forces had been attached to the culture of the community as part of its endeavor to maintain independence as soldiers and defense lines. The current upcoming challenge for the National Police of the Republic of Indonesia is to revitalize the concept of voluntary security through PAM Swakarsa that makes no room for social and political violence the group’s members and civilians without going through the proper judicial process, which goes against the values of patriotism, as well as the principles of Indonesia as a state based on the rule of law.AbstrakSaat ini, tajuk mengenai Pam Swakarsa kembali diangkat ke permukaan dan jadikan sebagai program andalan Polri sebagai usaha untuk mengimplementasikan paradigma community policing atau paradigma kemitraan antara polisi dan masyarakat sebagai elemen pengamanan swakarsa. Akan tetapi, momok dari Pam Swakarsa pada tahun 1998 yang kerap dilekatkan dengan pasukan yang tidak terikat hukum dan sumber dari pelaku-pelaku pelanggaran HAM, menjadi halangan terbesar di dalam badan kepolisian untuk menghidupkan kembali Pam Swakarsa di tengah-tengah masyarakat. Pasukan Pengamanan Swakarsa atau Pam Swakarsa pernah memainkan peran penting di dalam mengamankan Sidang Istimewa MPR RI yang diselenggarakan pada tahun 1998 silam. Secara historis, sebelum terbentuknya Pam Swakarsa, pasukan pengamanan sukarela telah melekat menjadi kultur di dalam masyarakat sebagai bagian dari unsur masyarakat untuk mempertahankan kemerdekaan sebagai laskarlaskar dan barisan-barisan pertahanan. Menjadi tantangan selanjutnya bagi Kepolisian Republik Indonesia untuk menciptakan konsep pengamanan sukarela Pam Swakarsa yang tidak membuka peluang bagi terjadinya kekerasan sosial dan politik antara unsur-unsur di dalam Pam Swakarsa dengan masyarakat sipil tanpa melalui proses hukum dan bertentangan dengan nilai-nilai nasionalisme dan kebangsaan serta bertentangan dengan asas Indonesia sebagai negara hukum.